2013
DOI: 10.1111/jen.12107
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific responses of Asian citrus psyllid to volatiles of conspecific and host‐plant origin

Abstract: Diaphorina citri Kuwayama (Hemiptera: Psyllidae) is the primary vector of Candidatus Liberibacter spp. bacteria that cause citrus greening, a disease of worldwide importance. Olfactometry was employed to test responses of D. citri to odours from intact citrus plants (Mexican lime, Citrus aurantifolia, sour orange, Citrus aurantium, Marsh grapefruit, Citrus paradisi and Valencia orange, Citrus sinensis), citrus plants previously infested with D. citri, and odours of conspecifics including nymphs, adult insects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 47 publications
0
6
0
1
Order By: Relevance
“…Once in close proximity, female-produced cuticular hydrocarbons, which appear to function as sex pheromones, attract males to engage in courtship and copulation [12,18,19]. It is likely that these pheromones function as short-distance cues used after vibrational communication has allowed long-distance detection along the plant surface.…”
Section: Introductionmentioning
confidence: 99%
“…Once in close proximity, female-produced cuticular hydrocarbons, which appear to function as sex pheromones, attract males to engage in courtship and copulation [12,18,19]. It is likely that these pheromones function as short-distance cues used after vibrational communication has allowed long-distance detection along the plant surface.…”
Section: Introductionmentioning
confidence: 99%
“…Wenninger et al [ 14 ] found that D. citri responded to visual stimuli in the absence of host-plant odor, suggesting that visual cues alone are sufficient to elicit attraction to host-plants. Nonetheless, D. citri is stimulated by host-plant odors [ 14 , 15 , 16 , 17 , 18 ] and olfaction seems to play some role in host-plant selection. The nature of that role, however, is not clear; i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Field observations showed that Citrus medical suffered the heaviest from D. citri , followed by Citrus sinensis , with Citrus reticulate the lightest 78 , 79 . Female D. citri orient to their plant of origin; males orient to the odor of females and co-specific excretions 80 . This behavior in combination with female oviposition preference behavior likely results in mate choice and limits gene flow between D. citri from different host plant clusters 81 , 82 .…”
Section: Discussionmentioning
confidence: 99%